2020
DOI: 10.1126/sciadv.aax3931
|View full text |Cite
|
Sign up to set email alerts
|

Decreased nonspecific adhesivity, receptor-targeted therapeutic nanoparticles for primary and metastatic breast cancer

Abstract: Development of effective tumor cell–targeted nanodrug formulations has been quite challenging, as many nanocarriers and targeting moieties exhibit nonspecific binding to cellular, extracellular, and intravascular components. We have developed a therapeutic nanoparticle formulation approach that balances cell surface receptor-specific binding affinity while maintaining minimal interactions with blood and tumor tissue components (termed “DART” nanoparticles), thereby improving blood circulation time, biodistribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 62 publications
3
93
1
Order By: Relevance
“…ITEM4 or Fn14 monoclonal antibody binds specifically human as well as murine Fn14 extracellular domain. Paclitaxel loaded-DART nanoparticles is an FDA-approved nanoformulation for TNBC models as well as an intracranial model thus indicating that there is TNBC growth which is followed by metastatic propagation to the brain [207]. Furthermore, Xu et al developed Hyaluronic acid-coated pH sensitive poly (Beta-amino ester) nanoparticles for the delivery of both embelin (anti-cancer drug) as well as pTRAIL (tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) plasmid for anti-TNBC efficacy [208].…”
Section: (Viii) Polymeric Nanoparticlesmentioning
confidence: 99%
“…ITEM4 or Fn14 monoclonal antibody binds specifically human as well as murine Fn14 extracellular domain. Paclitaxel loaded-DART nanoparticles is an FDA-approved nanoformulation for TNBC models as well as an intracranial model thus indicating that there is TNBC growth which is followed by metastatic propagation to the brain [207]. Furthermore, Xu et al developed Hyaluronic acid-coated pH sensitive poly (Beta-amino ester) nanoparticles for the delivery of both embelin (anti-cancer drug) as well as pTRAIL (tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) plasmid for anti-TNBC efficacy [208].…”
Section: (Viii) Polymeric Nanoparticlesmentioning
confidence: 99%
“…Another obstacle for tumor-targeted nanoformulations in particular is the heterogeneity and heterogeneous nature of tumors. Different gene expression profiles, molecular patterns and degree of drug resistance between different tumors may impede penetration and decrease the efficacy of tumor-targeted NPs [114,115]. This challenge could lead to an unsuccessful clinical trial (despite promising animal preclinical data) and to rejection of the nanoformulations examined.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…This challenge could lead to an unsuccessful clinical trial (despite promising animal preclinical data) and to rejection of the nanoformulations examined. Relevant drug penetration into tumors, the efficacy of the release of drugs into the target cells, and the quality of the drug loaded nanoparticles, are other factors that involve a precise professional experimentation [114]. Owing to time and money problems, this comprehensive research may not be possible in all biomedical laboratories which itself is another concern.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…In one study, a PTX loaded nanoscale polymer was designed to specifically target the cell surface receptor Fn14. Targeting to Fn14 enhanced the inhibition of breast tumors and significantly minimized the nonspecific binding to blood serum proteins and tumor tissue components [ 115 ]. Another study reported an RNA four-way junction NPs with ultra-thermodynamic stability covalently loaded with high-density PTX (RNA-PTX) for targeted cancer therapy.…”
Section: Application and Clinical Trials Of Nanocarrier-based Thermentioning
confidence: 99%